2021
DOI: 10.3389/fonc.2021.560506
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Validation of circRNA-miRNA Network in Regulating m6A RNA Methylation Modulators Reveals CircMAP2K4/miR-139-5p/YTHDF1 Axis Involving the Proliferation of Hepatocellular Carcinoma

Abstract: The m6A RNA methylation modulators play a crucial role in regulating hepatocellular carcinoma (HCC) progression. The circular RNA (circRNA) regulatory network in regulating m6A RNA methylation modulators in HCC remains largely unknown. In this study, 5 prognostic m6A RNA methylation modulators in HCC were identified from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) projects. The differentially expressed microRNAs (DEmiRNAs) and circRNAs (DEcircRNAs) between paired tumor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…In BC, the most studied function of circRNA is acting as tumor promoters or suppressors by miRNA sponges. Besides, emerging studies have identified the roles of circRNAs serving as miRNA sponges in the regulation of m6A RNA methylation modulators in various cancers, including hepatocellular carcinoma [ 10 ], gastric cancer [ 11 ], and adrenocortical carcinoma [ 12 ]. However, few studies have comprehensively investigated roles in the interaction of circRNAs and m6A in BC.…”
Section: Introductionmentioning
confidence: 99%
“…In BC, the most studied function of circRNA is acting as tumor promoters or suppressors by miRNA sponges. Besides, emerging studies have identified the roles of circRNAs serving as miRNA sponges in the regulation of m6A RNA methylation modulators in various cancers, including hepatocellular carcinoma [ 10 ], gastric cancer [ 11 ], and adrenocortical carcinoma [ 12 ]. However, few studies have comprehensively investigated roles in the interaction of circRNAs and m6A in BC.…”
Section: Introductionmentioning
confidence: 99%
“…confirmed that circMAP2K4 could act as miR-139-5p sponge to upregulate the expression and activity of YTHDF1 and promote HCC proliferation. 136 These findings enrich our understanding of the roles of RNA epigenetic regulation patterns.…”
Section: Roles Of Circrnas In the Regulation Of M 6 A Modificationmentioning
confidence: 85%
“…Chi et al. 65 validated that hsa_circ_0007456 (circMAP2K4) might facilitate HCC proliferation by sponging hsa-miR-139-5p to increase YTHDF1 expression.…”
Section: Circrnas Regulate M6a Modification In Cancermentioning
confidence: 99%